Exploring EFL Learners' Experiences of Using English Movies to Enhance Listening Skills - Siti Nurhaliza; Devi Mulatsih; Nunung Nurjannah (Journal of Educational Management Research, 2026)
This study aimed to explore EFL learners’ experiences of using English movies to enhance their listening skills, identify the benefits they gained, and examine the challenges they encountered during the learning process. A qualitative descriptive approach was employed to provide an in-depth understanding of learners’ experiences. The participants consisted of three undergraduate EFL students purposively selected from a private university in Indonesia. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that watching English movies significantly contributed to the improvement of learners’ listening skills by enhancing their comprehension of authentic spoken English, pronunciation, vocabulary acquisition, and awareness of various English accents. Furthermore, the participants reported increased motivation, confidence, and enjoyment in learning English through authentic audiovisual materials. Despite these benefits, they experienced several obstacles, including rapid speech, unfamiliar accents, connected speech, and limited vocabulary. To address these challenges, they adopted various learning strategies such as using subtitles, replaying difficult scenes, and inferring meaning from context. The study implies that integrating English movies into EFL instruction can provide an engaging and authentic learning environment that effectively supports listening development while fostering learners’ motivation and autonomous learning skills.